Ultraviolet Radiation and the Slug Transcription Factor Induce Proinflammatory and Immunomodulatory Mediator Expression in Melanocytes - Stephanie H. Shirley; Elizabeth A. Grimm; Donna F. Kusewitt (Journal of Skin Cancer)
Despite extensive investigation, the precise contribution of the ultraviolet radiation (UVR) component of sunlight to melanoma etiology remains unclear. UVR induces keratinocytes to secrete proinflammatory and immunomodulatory mediators that promote inflammation and skin tumor development; expression of the slug transcription factor in keratinocytes is required for maximal production of these mediators. In the present studies we examined the possibility that UVR-exposed melanocytes also produce proinflammatory mediators and that Slug is important in this process. Microarray studies revealed that both UVR exposure and Slug overexpression altered transcription of a variety of proinflammatory mediators by normal human melanocytes; some of these mediators are also known to stimulate melanocyte growth and migration. There was little overlap in the spectra of cytokines produced by the two stimuli. However IL-20 was similarly induced by both stimuli and the NFκB pathway appeared to be important in both circumstances. Further exploration of UVR-induced and Slug-dependent pathways of cytokine induction in melanocytes may reveal novel targets for melanoma therapy.